Dose Ethical Screening Sacrifice Financial Performance： Evidence From 13 Ethical Indices In Developed Markets - NIE, RUI (2013)
Ethical investors make their investment decisions based on both financial and ethical criteria, in order to ensure that the performances of their investment portfolios are consistent with their personal value system and beliefs. Do such investors pay a price for investing in ethical investment portfolios? This study examines the potential impact of ethical screening process on the stock portfolios by comparing 13 ethical indices from the developed stock markets with their relevant market benchmarks over a 12-year sample period of 2001-2013. The results indicate that the application of ethical screens does not necessarily sacrifice the financial performance.